Papers of Ron Tullipan - Tullipan, Ron, 1917-1975. (1956)
Contains a published copy of his novel Daylight Robbery, three issues of The Realist in which there are stories and/or articles by Tullipan, the typescript for an unpublished novel Wake-up place, newspaper clippings, novel The Sydneysiders published in instalments in the Australian Journal, the beginning of a revamping of this novel for 14 years olds.
Manuscript reference no. : MS 5364.
Novelist, died 1975.
Keywords: Tullipan, Ron, -- 1917-1975 -- Archives; Authors, Australian -- Archives; Novelists, Australian -- 20th century -- Archives; Novelists; Authors